The Effect Of Actıvator Treatment Of Skeletal Class 2 Malocclusıons On The Temporomandıbular Joınt Reactıon Force - Oktay Üner; Nilüfer Darendeliler; Haluk Darendeliler (Galenos Yayinevi, 1998)
A change in the pattern of condylar loading might lead to an increase in the amount of condylar/mandibular growth. In this study, the effect of activator treatment of skeletal Class 2 malocclusions on the magnitude and direction of the temporomandibular joint reaction force has been investigated. The treatment group for this study consisted of 12 patients, 8 girls and 4 boys, with an average age of 11.42 ± 0.29 years and skeletal age of 11.02 ± 0.29 years. An Andresen type activator was used for a mean period of 11 months. Electromyographic (EMG) activity of the masseter and anterior temporal muscles were measured and lateral cephalometric radiographs were taken at the beginning and at the end of the study. A two-dimensional model is described on the lateral cephalometric radiographs which uses the intregated EMG (IEMG) activity of the muscles and bite force as the input data and a computer program has been developed to calculate the magnitude and direction of the temporomandibular joint reaction force using this model. The differences of the magnitude and direction of the temporomandibular joint reaction force obtained at the beginning and at the end of activator treatment were compared with paired t-test but not found to be statistically significant.